Insight into the new infection pathway resulting from above-ground pathogen infection of grapevine crown gall - Kawaguchi, Akira (Frontiers in Plant Science, 2024)
Grapevine crown gall (GCG), a soil-borne plant disease caused by tumorigenic Allorhizobium vitis (TAV) (=tumorigenic Rhizobium vitis) strains, poses a significant threat to grapevines worldwide. Recently, outbreaks of GCG have been reported in several vineyards, necessitating investigation into potential alternative infection pathways beyond soil transmission. The spatiotemporal distribution of GCG in vineyards from 2020 to 2022 was analyzed using the binary power law (BPL) model, with variations in quadrat shapes. Both total and newly observed diseased plants exhibited an aggregated distribution, indicating that new infections clustered around existing diseased plants, with secondary infections appearing as independent cluster points. This study provides evidence that infected pruning tools can transmit the pathogen to healthy grapevines and that TAV inoculation through spraying contributes more to GCG incidence than planting in infected soil alone. This represents the first documented case of secondary above-ground TAV infection contributing to GCG in commercial vineyards.